2022
DOI: 10.1021/acs.langmuir.2c01057
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Water with Pristine and Defective MoS2

Abstract: Molybdenum disulfide (MoS 2 ) is a lamellar solid lubricant often used in aerospace applications because of its extremely low friction coefficient (∼0.01) in inert environments. The lubrication performance of MoS 2 is significantly impaired by exposure to even small amounts of water and oxygen, and the mechanisms behind this remain poorly understood. We use density functional theory calculations to study the binding of water on MoS 2 sheets with and without defects. In general, we find that pristine MoS 2 is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…This microstructural change is proposed to be a contributing factor to the observed changes in the extent of oxidation within the wear track for the case of MoS 2 samples that were pre-annealed and aged. This interpretation is supported by DFT calculations, which have shown that water adsorption is only thermodynamically favorable on Mo-terminated (100) edge planes 66 or defects such as sulfur vacancies or oxygen substitutions on (002) basal planes, 67 and indicated that sulfur-terminated (110) planes of MoS 2 are likely unfavorable for water adsorption. Moreover, flake oxidation studies have observed preferential oxidation with associated cleavage along (100) edge planes as opposed to (110) edge planes.…”
Section: Resultsmentioning
confidence: 74%
“…This microstructural change is proposed to be a contributing factor to the observed changes in the extent of oxidation within the wear track for the case of MoS 2 samples that were pre-annealed and aged. This interpretation is supported by DFT calculations, which have shown that water adsorption is only thermodynamically favorable on Mo-terminated (100) edge planes 66 or defects such as sulfur vacancies or oxygen substitutions on (002) basal planes, 67 and indicated that sulfur-terminated (110) planes of MoS 2 are likely unfavorable for water adsorption. Moreover, flake oxidation studies have observed preferential oxidation with associated cleavage along (100) edge planes as opposed to (110) edge planes.…”
Section: Resultsmentioning
confidence: 74%
“…To determine how much energy is associated with MoS 2 layer separation, we used DFT calculations (PBE functional, 520 eV, DFT details same as our previous work 37 ) on a 5 × 5 unit cell of MoS 2 with 4 layers in the 2H configuration (ESI Fig. 2 † ).…”
Section: Resultsmentioning
confidence: 99%
“…The MoS 2 structure was held fixed at the crystallographic minimum computed with density functional theory (DFT) (PAW_PBE pseudopotentials, 520 eV energy cutoff, and a 4 × 4 × 1 Monkhorst–Pack k -points grid) in our previous work. 37 The energy of separating layers of MoS 2 was computed using single point DFT calculations with the same parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several techniques have been applied to study the interaction and properties of water with graphite and 2D materials surfaces. Chiefly, among them were water contact angle, ,,, X-ray reflectivity, ,, electron microscopy, vibrational sum-frequency-generation spectroscopy, , X-ray spectroscopies, ,, AFM methods, 3D AFM, ,,,,, and impedance methods. ,,, The experimental techniques were complemented by a variety of theoretical and molecular dynamics methods. , , Nanofluidic channels made from two-dimensional crystals enabled the fabrication of devices that relied on the interfacial liquid water properties. , Those devices were also applied to study the interaction of water with graphene and hexagonal boron nitride surfaces. , …”
Section: Methods To Study Interfacial Water On Graphite and 2d Layere...mentioning
confidence: 99%